Freedom of Contract and Certainty of Sharia Law in IMBT: Perspectives on Indonesian and Malaysian Legal Culture - Yunari, Afrik; Choiriyah, Ana Laela Fatikhatul; Hidayat, Freddy (Kawanua International Journal of Multicultural Studies, 2025)
The development of Islamic financing through the Ijarah Muntahiyah Bittamlik (IMBT) contract shows fundamental differences in contract structure and regulatory approach between Indonesia and Malaysia, which have implications for the application of the principles of freedom of contract and certainty of Islamic law. The research gap is still evident in the lack of comparative studies linking the differences in the structure of the IMBT contract with legal culture, maqasid shariah, and judicial practices in Indonesia. This study aims to analyze and compare the application of the principles of freedom of contract and certainty of Islamic law in IMBT in Indonesia and Malaysia. The research method used is normative juridical with a comparative legal approach, through analysis of laws and regulations, fatwas of Islamic authorities, regulatory policies, and relevant court decisions. The research findings show that: (1) Indonesia emphasizes the formal separation of ijarah and tamlik contracts to maintain legal certainty and Islamic prudence; (2) Malaysia adopts an integrated wa'd- based contract structure with a substantive approach and is oriented towards maqasid shariah; and (3) these differences reflect variations in legal culture and sharia governance models in each country. The implications of this research emphasize the importance of harmonizing formal legal certainty and substantive interests in the development of IMBT contracts, in order to encourage sharia financing that is more adaptive, fair, and responsive to the dynamics of the Islamic financial industry.